2016
DOI: 10.1063/1.4964762
|View full text |Cite
|
Sign up to set email alerts
|

Droplet condensation on superhydrophobic surfaces with enhanced dewetting under a tangential AC electric field

Abstract: In this Letter, the dewetting behavior of superhydrophobic condensing surfaces under a tangential AC electric field is reported. The surface coverage of condensed droplets only exhibits a negligible increase with time. The jumping frequency of droplets is enhanced. The AC electric field motivates the dynamic transition of droplets from stretch to recoil, resulting in the counterforce propelling droplet jumping. The considerable horizontal component of jumping velocity facilitates droplet departure from superhy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…When the electric field strength reached 0.1 V/Å, the condensed cluster separated from the surface. This has also been found in experiment [56].…”
Section: Resultssupporting
confidence: 86%
“…When the electric field strength reached 0.1 V/Å, the condensed cluster separated from the surface. This has also been found in experiment [56].…”
Section: Resultssupporting
confidence: 86%
“…This is because the electrostatically charged condensation droplets are accelerated to detach from the solid surface under the application of the electric field. [ 96–98 ] It is has been demonstrated an enhanced heat transfer coefficient of 50% on a superhydrophobic CuO surface compared to conventional jumping‐droplet condensation (Figure 7f,g). [ 99 ] Last but not least, the droplet jumping from the superhydrophobic surfaces under the electric field also shows many promising applications, including self‐cleaning, [ 100 ] anti‐icing, [ 101 ] and ink‐printing.…”
Section: Electrohydrodynamic Effectmentioning
confidence: 99%
“…Additionally, the movement of water droplets can remove dirt particles from a surface [17][18][19], which makes the surface dry and clean, thus enhancing the insulation strength of the superhydrophobic coating. Previous studies in our group have focused on the electric field-driven self-propelled motion of water droplets on a superhydrophobic surface [20], and the droplet condensation on superhydrophobic surfaces under AC electric fields has also been investigated [21]. Vallabhuneni et al showed that superhydrophobic polydimethylsiloxane sheets could maintain dielectric strength under wet conditions [22].…”
Section: Introductionmentioning
confidence: 99%